Consequences of Amide Connectivity in the Supramolecular Polymerization of Porphyrins: Spectroscopic Observations Rationalized by Theoretical Modelling. Issue 37 (27th May 2021) - Weyandt, Elisabeth; Filot, Ivo A. W.; Vantomme, Ghislaine; Meijer, E. W.
Abstract: The correlation between molecular structure and mechanism of supramolecular polymerizations is a topic of great interest, with a special focus on the pathway complexity of porphyrin assemblies. Their cooperative polymerization typically yields highly ordered, long 1D polymers and is driven by a combination of π‐stacking due to solvophobic effects and hydrogen bonding interactions. Subtle changes in molecular structure, however, have significant influence on the cooperativity factor and yield different aggregate types (J‐ versus H‐aggregates) of different lengths. In this study, the influence of amide connectivity on the self‐assembly behavior of porphyrin‐based supramolecular monomers was investigated. While in nonpolar solvents, C=O centered monomers readily assemble into helical supramolecular polymers via a cooperative mechanism, their NH centered counterparts form short, non‐helical J‐type aggregates via an isodesmic pathway. A combination of spectroscopy and density functional theory modelling sheds light on the molecular origins causing this stunning difference in assembly properties and demonstrates the importance of molecular connectivity in the design of supramolecular systems. Finally, their mutual interference in copolymerization experiments is presented. Abstract : Amide connectivity in the molecular design of porphyrin supramolecular monomers strongly impacts the assembly behavior in nonpolar solvents. While C=O centered monomers aggregate cooperatively into long, 1D supramolecular fibers, their NH‐centered counterparts only form isodesmic J‐aggregates. With a combination of spectroscopy and density functional modelling, the authors shed light on the molecular origins of these differences in properties.